Dance of death - Preston, Douglas J.; Child, Lincoln (Preston, Douglas J. Pendergast novel, 2014)
"FBI Special Agent Pendergast is pitted against his most personal foe: His brother, Diogenes, has planned a horrendous crime and is framing Pendergast for a series of terrible murders."--Provided by the publisher.